An industrial quality control study of Oceana International - Bolotaolo, Gerald; Go, Timothy; Parale, Kristina (Diliman, Quezon City College of Engineering, 2005)
The Industrial Quality Control study of Oceana International aims to utilize the various concepts and principles of Industrial Quality Control to improve the quality and productivity of the company's production system. The study aims to apply statistical process control using both data available by the company, as well as those collected by the group. This data will allow the author's to analyze and recommend means for the company to improve the quality of their products. After the initial documentation and analysis of the company's current production system and interviews with the management of the company, it was determined that the major problem that the company was experiencing was a high frequency of reworking that goes into producing satisfactory units. There was also a lack of a comprehensive and effective quality management system, which was evident in the lack of data available from certain areas of production. Quality data in certain areas was not being gathered in the current system. Other problems observed by the group were a lack of safety equipment, material handling and storage equipment and deficiency in scrap collection and clean up. Based on the analysis of the problems, the authors developed several recommendations to better improve the production system and address these problems. The major recommendation given by the authors was the implementation of a comprehensive quality management system. This system includes the implementation of data gathering in all stages of production, as well as the use of control charts to monitor the process averages and capability of each process. Other recommendations include the acquisition of safety equipment and storage and handling equipment and the fabrication of scrap-catching devices to collect dirt. It was also recommended that the company install new ventilation devices to improve airflow in the company and the use of strict and clear standards, preferably through the use of pictures and illustrations, in the inspection of the product during the various stages of production. To be able to fully utilize and achieve the best results for these and any changes to be made by the company, it is recommended that management must take a definitive stand and take the initiative to promote and ensure that these changes are being implemented strictly by the workers.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Boats and boating equipment and supply; Quality control